Upregulated Wnt-11 and miR-21 Expression Trigger Epithelial Mesenchymal Transition in Aggressive Prostate Cancer Cells - RENCÜZOĞULLARI, ÖZGE; Freitas, Ines Lua; Radzali, Syanas; Keskin, Buse; Kothari, Archana; Warford, Antony; Uysal-Onganer, Pınar; ARISAN, ELİF DAMLA (MDPI, 2020)
Prostate cancer (PCa) is the second-leading cause of cancer-related death among men. microRNAs have been identified as having potential roles in tumorigenesis. An oncomir, miR-21, is commonly highly upregulated in many cancers, including PCa, and showed correlation with the Wnt-signaling axis to increase invasion. Wnt-11 is a developmentally regulated gene and has been found to be upregulated in PCa, but its mechanism is unknown. The present study aimed to investigate the roles of miR-21 and Wnt-11 in PCa in vivo and in vitro. First, different Gleason score PCa tissue samples were used; both miR-21 and Wnt-11 expressions correlate with high Gleason scores in PCa patient tissues. This data then was confirmed with formalin-fixed paraffin cell blocks using PCa cell lines LNCaP and PC3. Cell survival and colony formation studies proved that miR-21 involves in cells' behaviors, as well as the epithelial-mesenchymal transition. Consistent with the previous data, silencing miR-21 led to significant inhibition of cellular invasiveness. Overall, these results suggest that miR-21 plays a significant role related to Wnt-11 in the pathophysiology of PCa.
Keywords: microRNA; In Situ Hybridization; Prostate Cancer; Wnt-11; miR-21